Work Challenges Among Hotel and Restaurant Management Staff - Pacatang, Francis Jun A.; Zapanta, Mc Andrew E.; Espinola, Prince Jacob M.; Lomostre, Ma Lilian P. (Randwick International of Social Science Journal, 2024)
Understanding and addressing these challenges is essential for the employees and the industry. The study was conducted to determine the work challenges among hotel and restaurant management staff in Butuan City. The researchers employed a descriptive comparative approach for this study. Based on the findings, there is a moderate extent of work challenges among hotel and restaurant management staff in Butuan City. This means that the extent of challenges sometimes coincides with the respondents’ experience. In addition, there is no significant difference in the work challenges faced by the hotel and management staff in Butuan City. Moreover, the challenges faced by hotel and restaurant management staff in Butuan City. The data reveals that lack of recognition as the top challenge; poor communication and work schedules are also significant challenges. Furthermore, Herzberg's Two-Factor Theory supports the study's findings by highlighting the importance of addressing both hygiene factors and motivators. Since the findings show that the hotel and restaurants lack recognition, to address the challenge of lack of recognition, hotel and restaurant management should implement a structured employee recognition program. This program can include monthly or quarterly awards, shout-outs during meetings, or employee of the month acknowledgments.